“Modernization” and Agrarian Development in India, 1912–52 - Kumar, Prakash (The Journal of Asian studies, 2020)
India's agrarian history has for the most part been cast within colonial and nationalist frameworks or in analyses of modernity and development in the South Asian historiography on both sides of the independence divide. This leaves plenty of space to discuss both the vast engagement of American actors with Indian elite formations and modifications to the agrarian projects contingent upon those interactions. A focus on the Americanist drive for agrarian modernization in India allows for exploring the distinct cultural location of modernization in a long-term perspective and its engagement with colonial “development.” A study of their mutual interaction gives insights into modernization's somewhat distinct itinerary on the subcontinent and provides specificity to the history of the otherwise spatially wider American intervention in global and inter-Asian contexts.